Pengaruh Pelatihan Goal Setting Dalam Mengatasi Academic Boredom di Remaja Sidodadi Surabaya - Sheren Reggyna Herawan; Nabila Aurelia Rizqulah Sugijanto; Audrey Vivian Chandra; Sherly Yuriko Kato; Emre Omar Khaled; Livia Yuliawati; Tifani Meilianawati; Putri Ayu Puspieta; Mopheta Audiola Dorkas (Psychopreneur Journal, 2022)
During the pandemic, online learning led to the emergence of academic boredom due to the absence of face-to-face meetings. The existence of this boredom can reduce students' academic achievement, and can cause confusion in life purpose since they do not understand their goals. This study aims to determine the effect of goal setting training on academic boredom. The researcher used a purposive sampling technique with 10 participants aged 12-16 years in the "X" community. The training consisted of 3 meetings in 2 weeks. The measuring instrument that we used is the Academic Boredom Survey (ABS-10) with pre-test post-test control group designs. The results of the hypothesis test can be accepted because the p < .05 which is p = .009. There was an increase in the average score of the pre-test post-test from 35.6 to 55.3. On the other hand, where academic boredom should have decreased, it has actually increased. This may be due to the inconsistent attendance of participants at each training meeting.